Low-Complexity Massive MIMO Tensor Precoding - Ribeiro, Lucas N.; Schwarz, Stefan; de Almeida, Andre L. F.; Haardt, Martin (Conference record - Asilomar Conference on Signals, Systems, & Computers, 2020)
We present a novel and low-complexity massive multiple-input multiple-output (MIMO) precoding strategy based on novel findings concerning the subspace separability of Rician fading channels. Considering a uniform rectangular array at the base station, we show that the subspaces spanned by the channel vectors can be factorized as a tensor product between two lower dimensional subspaces. Based on this result, we formulate tensor maximum ratio transmit and zero-forcing precoders. We show that the proposed tensor precoders exhibit lower computational complexity and require less instantaneous channel state information than their linear counterparts. Finally, we present computer simulations that demonstrate the applicability of the proposed tensor precoders in practical communication scenarios.